The Points of Concurrence Theory in Guidobaldo del Monte’s Scenography (diségno, 2018)
Theatrical scenography was one of the privileged applications of perspective in the Renaissance. The court theater, characteristic of those years, is structured around a frontal perspective installation developed in depth. This particular perspective application makes the scenography a privileged place for experimenting the projective transformations at the origins of the relief perspective in which the real space contracts and transforms itself into the illusory space of the scene. This study regards the De scenis, the sixth book of Perspectivae libri sex, written by Guidobaldo del Monte in 1600, entirely devoted to theatrical scenography. The treatise elaborates a scientific method of universal validity to construct scenes, based on the theory of the points of concurrence explained in the first book of this work, a theory that deeply influenced the history of perspective and descriptive geometry. In Guidobaldo’s work, the problem of controlling the projective transformations of space is resolved by reducing the relief perspective to a set of flat perspectives in relation to each other and controlled through the theory of points of concurrence. Applied to the art of scenography, this theory reveals itself in all its generality, since it allows the representation of classes of lines generically oriented in space and, at the same time, resolves the problem of measuring angles and lengths with projective reasoning.
Keywords: Perspective; scenoraphy; Guidobaldo del Monte; Relief perspective; points of concurrence; prospettiva solida